Optical tracking and detection of immunomagnetically selected and aligned cells - Tibbe, Arjan G.J.; Grooth, Bart G. de; Greve, Jan; Liberti, Paul A.; Dolan, Gerald J.; Terstappen, Leon W.M.M. (Nature biotechnology, 1999)
We have developed a platform for cell analysis based on immunomagnetic selection and magnetic alignment of cells in combination with an epi-illumination tracking and detection system. Whole blood was labeled with ferromagnetic nanoparticles and fluorescent probes, and placed in a magnetic field in a chamber. Cells labeled with ferromagnetic nanoparticles moved upward and aligned along ferromagnetic lines deposited by lithographic techniques on an optically transparent surface of the chamber. An epi-illumination system using a 635 nm laser diode as a light source scanned the lines and measured signals obtained from the aligned cells. The cell counts per unit of blood volume obtained with the system correlated well with those obtained from the counts from a standard hematology analyzer and flow cytometer. The cell analysis platform is significantly less complex and more sensitive than current cell analysis equipment and provides additional functionality through its ability to subject the cells to repeated and varied analyses while they remain in a natural environment (i.e., whole blood).